2012
DOI: 10.1051/epjpv/2012009
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary process development towards next generation crystalline silicon solar cells : a semiconductor process toolbox application

Abstract: Bulk crystalline Silicon solar cells are covering more than 85% of the world's roof top module installation in 2010. With a growth rate of over 30% in the last 10 years this technology remains the working horse of solar cell industry. The full Aluminum back-side field (Al BSF) technology has been developed in the 90's and provides a production learning curve on module price of constant 20% in average. The main reason for the decrease of module prices with increasing production capacity is due to the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…John et al have reported that anti-reflection coating produced with the silane free precursor from Sixtron Applied Materials in solar cell production. Using it in the rear side passivation stack on top of SiO x , best cell results in local Al BSF solar cells have been measured around ~ 18% [19].…”
Section: Oxide Passivation and Nanostructure Synthesismentioning
confidence: 99%
“…John et al have reported that anti-reflection coating produced with the silane free precursor from Sixtron Applied Materials in solar cell production. Using it in the rear side passivation stack on top of SiO x , best cell results in local Al BSF solar cells have been measured around ~ 18% [19].…”
Section: Oxide Passivation and Nanostructure Synthesismentioning
confidence: 99%
“…Despite their relative maturity, solar cells and photovoltaic modules based on mono-or polycrystalline silicon still have potential for improvement, in terms of higher conversion efficiency as well as in terms of cheaper manufacturing [1]. Here we present experimental results on an interconnection method of solar cells, which permits higher power output per module area and may also lower production costs.…”
Section: Introductionmentioning
confidence: 98%
“…The need for cheaper levelized cost of PV-originated electricity (LCOE) and to finally reach grid parity translates in a need for cheaper solar cells with an increase in conversion efficiency [1]. In order to reach this goal novel cell concepts and novel fabrication methods have to be developed for implementation in industrial process lines [2]. In this context wet processes should also evolve towards easy to implement, well controlled and cost effective steps [3,4].…”
Section: Introductionmentioning
confidence: 99%